2017
DOI: 10.1186/s13018-017-0601-4
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative systemic steroid for rapid recovery in total knee and hip arthroplasty: a systematic review and meta-analysis of randomized trials

Abstract: BackgroundPerioperative systemic steroid administration for rapid recovery in total knee and hip arthroplasty (TKA/THA) is an important and controversial topic. We conducted this systematic review and meta-analysis to evaluate the overall benefits and harms of perioperative systemic steroid in patients undergoing TKA and THA.MethodsA comprehensive search was performed on PubMed, OVID, and Web of Science databases, and a systematic approach was carried out starting from the PRISMA recommendations. Relevant rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 35 publications
0
56
0
1
Order By: Relevance
“…It is well-known that pain is an important in uencing factor for patients' satisfaction with surgery. In the trial, the same enhanced recovery after surgery and postoperative rehabilitation training were used in all groups [27,28]. The analysis of the results showed that the visual analogue scale at 1, 3 and 7 d after the second half of tourniquet application was signi cantly greater than that in the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that pain is an important in uencing factor for patients' satisfaction with surgery. In the trial, the same enhanced recovery after surgery and postoperative rehabilitation training were used in all groups [27,28]. The analysis of the results showed that the visual analogue scale at 1, 3 and 7 d after the second half of tourniquet application was signi cantly greater than that in the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…4 Interest has recently grown in the perioperative systemic use of steroids in patients undergoing total knee and hip replacement, with a number of well-designed studies, systematic reviews and metanalyses being published. 6,11,17 However it is di cult to make comparisons between studies due to the variation in the doses and types of steroids used, as well as the timing of administration. A meta-analysis of randomized trials by Yue et al con rmed that steroid injections offer positive bene ts in terms of lower incidence of postoperative nausea and vomiting, as well as reduction of acute postoperative pain, hospital stay, without signi cant complications or adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone (DEX), with a strong anti‐inflammatory agent, has been widely used to reduce inflammatory markers, prevent PONV, and relieve postoperative pain and fatigue in various perioperative periods. Many previous randomized controlled trials (RCT) and meta‐analyses have demonstrated the effectiveness of DEX in preventing inflammatory stress, without the disadvantages of the wound and gastrointestinal bleeding complications in THA. The combined application of DEX and TXA has been reported in a few studies; however, the additional effects of the combined administration are not completely clear.…”
Section: Introductionmentioning
confidence: 99%